Does absorptive capacity moderate the relationship between entrepreneurial orientation and supply chain resilience? - Majid M. Goaill; Mohammed Al-Hakimi (Cogent Business & Management, 2021)
Supply chain resilience (SCR) is often seen as a dynamic capability that enables firms to effectively cope with disruptions and unforeseen events in the business environment. However, empirical research focusing on influencing factors on SCR is still limited. Based on the resource-based view (RBV) and the dynamic capabilities theory (DCT), we examine if absorptive capacity (AC) does in fact moderate the relationship between entrepreneurial orientation (EO) and SCR. Drawing upon a sample of 171 Yemeni manufacturing SMEs, we tested the relationships in the proposed model. The findings of the data analysis using SmartPLS show that EO positively affects SCR, further, AC positively moderates the relationship between EO and SCR. With this outcome, it is expected that SME managers in Yemen demonstrate significant interest in developing the AC of their firms. This has implications that with the development of AC, it is expected that SMEs will be able to utilize the full potential of EO to improve SCR.
Keywords: G24; G32; L25; 650; Entrepreneurial Orientation; Absorptive Capacity; Supply Chain Resilience; SMEs; PLS-SEM